This lesson will act as a summary of all the previous lessons in this unit for how to determine the y-value and the x-values/roots of quadratic equations using the various different methods.

## Quadratic Formula

We can determine the roots of a quadratic equation using the given formula:

\(x = \cfrac{-\textcolor{green}{b} +- \sqrt{\textcolor{green}{b}^2 - 4\textcolor{red}{a}\textcolor{blue}{c}}}{2\textcolor{red}{a}}\)
This formula is useful for determining the zeroes of a parabola or when it's difficult to factor a quadratic equation. Remember to set the equation to 0 before determining the values of \(\textcolor{red}{a},\textcolor{green}{b},\) and \(\textcolor{blue}{c}\).

Determine the y-intercept and x-intercepts of \(2c² + 7c = 4\) using the quadratic formula. Then, graph the correpsonding parabola based on these intercepts.

Show Answer
First, we can shift all terms onto one side:

\(y = \textcolor{red}{2c²} + \textcolor{green}{7c} \textcolor{blue}{- 4}\)
Next, we can use the quadratic formula to determine the roots. In this instance, \(\textcolor{red}{a = 2}\), \(\textcolor{green}{b = 7}\) and \(\textcolor{blue}{c = -4}\).

\(x = \cfrac{-\textcolor{green}{b} \pm \sqrt{\textcolor{green}{b}^2 - 4\textcolor{red}{a}\textcolor{blue}{c}}}{2\textcolor{red}{a}}\)

\(x = \cfrac{-(\textcolor{green}{7}) \pm \sqrt{(\textcolor{green}{7})^2 - 4(\textcolor{red}{2})(\textcolor{blue}{-4})}}{2(\textcolor{red}{2})}\)

\(x = \cfrac{-7 \pm \sqrt{49 + 32}}{4}\)

\(x = \cfrac{-7 \pm \sqrt{81}}{4}\)
Using ±, we can determine the 2 roots either by adding the 2 values of subtracting the 2 values:

\(x_1 = \cfrac{-7 + 9}{4}\)

\(x_1 = \cfrac{2}{4}\)

\(x_1 = \cfrac{1}{2}\)

\(x_2 = \cfrac{-7 - 9}{4}\)

\(x_2 = \cfrac{-16}{4}\)

\(x_2 = -4\)
We can now determine the y-intercept by setting \(x = 0\)

\(y = 2(0)² + 7(0) - 4\)

\(y = - 4\)
In order to determine the vertex, we first need to identify the Axis of Symmetry. We can do this by dividing the sum of the x-intercepts by 2:

\(\text{AOS} = \cfrac{1/2 - 4}{2}\)

\(\text{AOS} = \cfrac{-7/2}{2}\)

\(\text{AOS} = \cfrac{-7}{4}\)
We can plug this value into the original equation to determine the Optimal Point:

\(\text{OP} = 2(\cfrac{-7}{4})² + 7(\cfrac{-7}{4}) - 4\)

\(\text{OP} = 2(\cfrac{49}{16}) - \cfrac{49}{4} - 4\)

\(\text{OP} = \cfrac{98}{16} - \cfrac{196}{16} - \cfrac{64}{16}\)

\(\text{OP} = \cfrac{-162}{16}\)
As we determined that the vertex is \((\cfrac{-7}{4}\), \(\cfrac{-162}{16}\), we can now draw our graph:

## Standard Form

The Standard Form of a quadratic equation is expressed as such:

\(y = ax² + bx + c\)
In order to determine the x-intercepts, we need to fully factor the equation or use the Quadratic Equation.
In order to determine the y-intercept, we need to set \(x = 0\) and solve for \(y\).

Determine the y-intercept and x-intercepts of \(y = 3x² - 12x + 9\). Then, graph the correpsonding parabola based on these intercepts.

Show Answer
First, we can easily factor this equation in order to determine the x-intercepts:

\(y = 3x² - 3x - 9x + 9\)

\(y = 3x(x - 1)-9(x - 1)\)

\(y = (x - 1)(3x - 9)\)

\(y = 3(x - 1)(x - 3)\)
We can determine the roots as 1 and 3. We can now determine the y-intercept:

\(y = (3(0)² - 12(0) + 9\)

\(y = 9\)
In order to determine the vertex, we first need to identify the Axis of Symmetry. We can do this by dividing the sum of the x-intercepts by 2:

\(\text{AOS} = \cfrac{3 + 1}{2}\)

\(\text{AOS} = \cfrac{4}{2}\)

\(\text{AOS} = 2\)
We can substitute the AOS for \(x\) in the original equation to determine the Optimal Point:

\(\text{OP} = 3(2)² + -12(2) + 9\)

\(\text{OP} = (3)(4) - 24 + 9\)

\(\text{OP} = 12 - 24 + 9\)

\(\text{OP} = -3\)
As we determined that the vertex is \((1, -3)\), we can now draw our graph:

## Factored Form

The Factored Form of a quadratic equation is expressed as such:

\(y = a(x - p)(x - q)\)
The x-intercepts are \(p\) and \(q\) which will make the equation equal \(0\).
The y-intercept can be determined by setting \(x = 0\), then solving for \(y\).

Determine the y-intercept and x-intercepts of \(y = -\cfrac{1}{2}(x-3)(x-7)\). Then, graph the correpsonding parabola based on these intercepts.

Show Answer
Based on the given equation, we can easily determine the x-intercepts:

\(x₁ = 3\)

\(x₂ = 7\)
We can now determine the y-intercept:

\(y = -\cfrac{1}{2}(0-3)(0-7)\)

\(y = -\cfrac{1}{2}(-3)(-7)\)

\(y = -\cfrac{1}{2}(21)\)

\(y = -\cfrac{21}{2}\)
In order to determine the vertex, we first need to identify the Axis of Symmetry. We can do this by dividing the sum of the x-intercepts by 2:

\(\text{AOS} = \cfrac{3 + 7}{2} = \cfrac{10}{2} = 5\)
We can substitute the AOS for \(x\) in the original equation to determine the Optimal Point:

\(\text{OP} = -\cfrac{1}{2}(5-3)(5-7)\)

\(\text{OP} = -\cfrac{1}{2}(2)(-2)\)

\(\text{OP} = -\cfrac{1}{2}(-4)\)
\(\text{OP} = 2\)

As we determined that the vertex is \((5, 2)\), we can now draw our graph:

## Vertex Form

The Vertex Form of a quadratic equation is expressed as such:

\(y = a(x - h)² + k\)
The vertex is already provided with \(h\) representing the x-coordinate and \(k\) representing the y-coordinate.
The y-intercept can be determined by setting \(x = 0\).
Depending on the equation, there may be 0, 1 or 2 x-intercepts.

Determine the y-intercept and x-intercepts of \(y = -2(x + 4)² + 3\). Then, graph the corresponding parabola based on these intercepts.

Show Answer
Based on the given equation, we can determine the y-intercept:

\(y = -2(0 + 4)² + 3\)

\(y = -2(4)² + 3\)

\(y = -2(16) + 3\)

\(y = -32 + 3\)

\(y = 29\)
Since the equation is shifted upwards and has a negative sign we can determine that this equation has x-intercept(s).:

\(-2(x + 4)² = -3\)

\(\cfrac{-2(x + 4)²}{-2} = \cfrac{-3}{-2}\)

\(\sqrt{(x + 4)²} = \sqrt{\cfrac{3}{2}}\)

\(x + 4 = \sqrt{\cfrac{3}{2}}\)

\(x = 4 +- \sqrt{\cfrac{3}{2}}\)
We can determine the 2 x-intercepts either by adding or subtracting the value from \(-4\):

\(x₁ = -4 -\sqrt{\cfrac{3}{2}}\)

\(x₁ = -5.22\)

\(x₂ = -4 + \sqrt{\cfrac{3}{2}}\)

\(x₂ = -2.78\)

Therefore, we can determine that the x-intercepts are \(-5.22\) and \(-2.78\) and the y-intercept is \(29\).

We can identify the vertex from the given equation, which is \((-4, 3)\).

With all values identified, we can now draw our graph: